Improving the Quality of Education Through the Competence of School Administrative Staff - Lutfiah, Lailatul; Maisyaroh, Maisyaroh; Benty, Djum Djum Noor (Universitas Negeri Malang, 2024)
Many schools tend to focus on the development of teachers and the curriculum, while administrative staff often do not receive adequate training and support. This leads to inefficiencies in data management, communication, finance, and resources, which can ultimately hinder the educational process. With training and professional development, administrative staff can play an important role in enhancing their competencies. As a result, investing in the development of administrative staff competencies will improve school performance and overall student academic achievement. Thus, the quality of education from an institution will develop well. This research aims to determine the influence of school administrative staff competence on the quality of education and to provide insights for education stakeholders on how to maximize the role of administrative staff in improving educational quality. The method used in this research is a qualitative approach with data collection through literature study, which involves gathering data from several sources such as books, journals, and previous research. This research shows that the competence of school administrative staff has a significant impact on the quality of education. Competent administrative staff can efficiently manage the school management system, accurately handle data and finances, and leverage information technology to expedite administrative processes.